Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I keep getting the following equation wrong: enter image description here

Firstly, I solve for y = x - 4, and substitute it in the second equation. Then once I get x from the second equation, I substite it back into the first equation, and get y.

However, my solution set shows that their are two possible answers for each x and y in this simultaneous equation. How is that possible?

Another question - can all equations that can be solved by elimination also be solved by substitution?

Will this be hard?

share|cite|improve this question
The first equation gives $y=\frac{4}{x}$. – Joe Johnson 126 Jun 10 '14 at 11:15
up vote 1 down vote accepted

$$xy = 4 \implies \frac 1x\cdot xy = \frac 1x\cdot 4 \iff y = \frac 4x$$

Why not use $2x - y - 7 = 0$ and solve for $y$:

$$y = 2x - 7$$

Now, substitute $y = 2x - 7$ into $xy = 4$ to get $$x(2x - 7) = 4 \iff 2x^2 - 7x - 4 = 0$$

Now you have a quadratic in $x$ to solve. It can be factored: $$\begin{align} 2x^2 - 7x - 4 = 0 &\iff (2x +1)(x - 4) = 0 \\ \\ & \iff (2x+1) = 0,\; \text{or} \;(x -4)= 0\\ \\ &\iff x = -\frac 12 \;\text{ or } x = 4\end{align}$$

(Or, it's perfectly legitimate to use the quadratic formula to solve for $x$.)

Finally, for each solution $x$, substitute into one of the original equations to solve for $y$. And yes, you will find two ordered pairs that solve both equations.

Two solutions?

That's because $xy = 4 \iff y = \frac 4x$ is a hyperbola. If you graph both equations, you'll see that the line $y = 7x-4$ intersects the hyperbola $y = \frac 4x$ in two points, your solutions. If both equations were of lines (non-parallel, non-coincident), then you'd be certain to have exactly one point of intersection.

share|cite|improve this answer

An alternate solution would be to solve for $y$ in the second equation:


Then substitute the result into the first equation:



share|cite|improve this answer

The problem in your answer is that $xy=4$ does not imply $y=x-4$. Instead, you should get, from the first equation, that


Or, if it is easier for you to solve from there, you could also use $x=\frac{4}{y}$ in the second equation. However, don't try to substitute both in.

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.